The Effect of Single Bout of Acute Exercise on Working Memory Performance - Deo, Santosh Kumar; Agrawal, Kopila; Bhattrai, Prem; Chaudhary, Raju Kumar (Birat Journal of Health Sciences, 2018)
Introduction: Working memory is a kind of short term memory important for reasoning and guiding decision-making and behavioral process.Objective: The goal of the present research was to study the outcome of single bout of acute moderate-intensity exercise on working memory.Methodology: Twenty two male subjects were asked to perform working memory task by 2n back task in baseline resting, immediately after exercise and after five minute of exercise session. 3 minute step test procedure was used as a moderate intensity exercise intervention.Results: The percentage correctness of 2n back task of working memory was found to be 64.36% for baseline resting condition, 78.01 % for immediately after 3-minute step test and 80.70% for 5 minute after the exercise. In both exercise session (i.e. immediately after exercise and after 5 minute of exercise), significant improvement (p value